2018
DOI: 10.1007/s00436-018-5762-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel Henneguya spp. (Cnidaria: Myxozoa) from cichlid fish in the Amazon basin cluster by geographic origin

Abstract: We describe three new Henneguya spp. (Myxobolidae) found parasitizing two species of cichlid fish from the Amazon basin, Brazil: H. tucunarei n. sp. from gill filaments of Cichla monoculus and H. tapajoensis n. sp. from gill filaments of Cichla pinima, both from the Tapajós River, Pará State and H. jariensis n. sp. in the fins of Cichla monoculus from the Jari River, Amapá State. We based descriptions on myxospore morphology and small subunit ribosomal DNA sequences, and used a phylogenetic analysis to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
7
0
3
Order By: Relevance
“…As a matter of fact, several studies on South American freshwater fish have corroborated this finding. For instance, Zatti et al (2018a), in a study conducted on the myxobolids of two Amazonian cichlids, Cichla monoculus Spix & Agassiz, 1831 and Cichla pinima Kullander & Ferreira, 2006 collected in different areas of the Brazilian part of the Amazon Basin, reported that in the lower Tapajós region, where both fish species are sympatric, the species Henneguya tapajoensis Zatti, Atkinson, Maia, Bartholomew & Adriano, 2018 was found infecting only C. pinima. Likewise, Adriano et al (2002), studying myxosporeans of four different characiforms confined in a cultured pond (Prochilodus lineatus Valenciennes, 1836, Piaractus mesopotamicus Holmberg, 1887, Brycon cephalus Günther, 1869 and Leporinus copelandii Steindachner, 1875), reported Myxobolous porofilus Adriano, Arana, Ceccarelli & Cordeiro, 2002 infecting exclusively Prochilodus lineatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, several studies on South American freshwater fish have corroborated this finding. For instance, Zatti et al (2018a), in a study conducted on the myxobolids of two Amazonian cichlids, Cichla monoculus Spix & Agassiz, 1831 and Cichla pinima Kullander & Ferreira, 2006 collected in different areas of the Brazilian part of the Amazon Basin, reported that in the lower Tapajós region, where both fish species are sympatric, the species Henneguya tapajoensis Zatti, Atkinson, Maia, Bartholomew & Adriano, 2018 was found infecting only C. pinima. Likewise, Adriano et al (2002), studying myxosporeans of four different characiforms confined in a cultured pond (Prochilodus lineatus Valenciennes, 1836, Piaractus mesopotamicus Holmberg, 1887, Brycon cephalus Günther, 1869 and Leporinus copelandii Steindachner, 1875), reported Myxobolous porofilus Adriano, Arana, Ceccarelli & Cordeiro, 2002 infecting exclusively Prochilodus lineatus.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zatti et al (2018a), host behavior may drive both parasite endemism and the radiation of myxosporeans within the Amazon Basin. These authors observed differences in the number of host species infected by a given species of myxosporean in a study conducted on species of the genus Cichla Schneider, 1801, which have differences in their distribution within the Amazon Basin.…”
Section: Discussionmentioning
confidence: 99%
“…Los Myxozoa Grassé, 1970 son un grupo de cnidarios endoparásitos con complejos ciclos de vida, que afectan diversos órganos de huéspedes vertebrados e invertebrados y que presentan alta especificidad (László et al, 2002;Okamura et al, 2018) y que han recibido una notoria atención en los últimos años (Araújo et al, 2022). Según estimaciones de Okamura et al (2018) se han descrito alrededor de 150 mixozoos de agua dulce en América del Sur, con alrededor de 55 reportados en la cuenca amazónica (Zatti et al, 2018).…”
Section: Myxozoaunclassified
“…Del género Henneguya Thélohan, 1892 podemos afirmar que es el segundo más grande dentro de los Myxosporea, con alrededor de 190 especies descritas a nivel mundial (Eiras & Adriano, 2012) que se caracterizan por ser predominantemente histozoicas, es decir, que son capaces de ocasionar considerables cambios patológicos como la destrucción de filamentos branquiales y ocasionar fallo respiratorio en el huésped (Lom & Dyková, 1992;Morsy et al, 2012;Mathews et al, 2016). Por su parte, los Ceratomyxa Thélohan, 1892 son ampliamente conocidos como parásitos de peces de aguas marinas y salobres; sin embargo, estudios recientes han revelado una creciente diversidad de especies de Ceratomyxa en las vesículas biliares de peces de agua dulce sudamericanos (Zatti et al, 2017;Zatti et al, 2018;Ferreira et al, 2021;Zatti et al, 2022;Araújo et al, 2022).…”
Section: Myxozoaunclassified
“…For example, 18S sequence data were used to reclassify Babesia equi as Theileria equi [8]. 18S sequence data have been used to identify and classify several previously unknown haemoprotozoans and other eukaryotic parasites in many other studies including, but not limited to, Persing [9], Quick et al [10], Thomford et al [11], Herwaldt et al [12], Katzer et al [13], Gubbels et al [14], Nijhof et al [15], Moss et al [16], Jorger & Schrodl [7], Ryan et al [17], Boscaro et al [18] and Zatti et al [19].…”
Section: Letter To the Editormentioning
confidence: 99%